PENINGKATAN KEMAMPUAN PENATAUSAHAAN DAN PELAPORAN BAGI APARAT PENGELOLA KEUANGAN PUSKESMAS DI KABUPATEN ENREKANG - Syamsuddin; Rahmawati HS; Hermita Arief; Ade Ikhlas (LP2M Universitas Hasanuddin, 2023)
Local Government financial statement is prepared to provide relevant information regarding the financial position and all transactions carried out during one reporting period. It provides information that is useful for users in assessing accountability as well as making economic, social and political decisions. To be able to carry out sound financial administration and reporting in accordance with laws and regulations, especially the applicable Government Accounting Standards (Standar Akuntansi Pemerintahan – SAP)), it is necessary for the local government to be supported by various aspects such as qualified human resources (HR), relevant regulation system and up-to-date infrastructure. The majority of staffs in charge for financial administration and reporting at the public health center (Puskesmas) in Enrekang do not possess accounting education background so they are facing difficulty in preparing financial statement or other accountability reports. It raised an urgency to provide relevant trainings for the staffs. The purpose of the training was to improve the understanding and insight of the responsible staffs at Puskesmas of Enrekang Regency regarding financial management in particular financial administration and reporting according to the Government Accounting Standards (SAP). The training was conducted on July 23, 2021 in Departement of Health at Enrekang Regency. It involved technical guidance employing lecture, discussion, and case exercise method. The results showed that, after the training, there was an increase in the understanding and ability of the staffs in carrying out financial administration and reporting which were their main duties and functions. — Laporan keuangan untuk pemerintah daerah dibuat untuk memberikan rincian yang relevan tentang situasi keuangan dan semua transaksi yang dilakukan dalam satu periode pelaporan. Untuk menilai tanggung jawab dan membuat keputusan pada tingkat ekonomi, sosial, dan politik, Konsumen laporan dapat memperoleh manfaat dari informasi yang diberikan oleh pelaporan keuangan pemerintah daerah.Untuk dapat melaksanakan penatausahaan dan pelaporan keuangan yang baik sesuai dengan peraturan perundang-undangan khususnya Standar Akuntansi Pemerintahan (SAP) yang berlaku, perlu ditunjang oleh berbagai aspek yang perlu dimiliki oleh Pemerintah Daerah sebagai penunjang pelaksana. Aspek-aspek tersebut diantaranya adalah sumber daya manusia (SDM) yang berkualitas, paket regulasi yang relevan dan infrastruktur yang uptodate. Mayoritas pelaksana penatausahaan dan pelaporan keuangan di puskesmas di Enrekang tidak berlatar belakang pendidikan akuntansi sehingga mengalami kesulitan dalam membuat pertanggungjawaban atau laporan keuangan. Oleh karena itu menjadi suatu hal yang penting untk melakukan upaya pelatihan bagi mereka. Tujuan kegiatan pelatihan yang dilakukan adalah dalam rangka meningkatkan pemahaman dan wawasan aparat pengelola keuangan Puskesmas di Kabupaten Enrekang mengenai pengelolaan keuangan khususnya penatausahaan dan pelaporan keuangan yang sesuai dengan SAP. Kegiatan bimbingan teknis memanfaatkan teknik penyampaian materi, diskusi dan studi kasus untuk menyelesaikan kasus-kasus pengelolaan keuangan. Pada tanggal 23 Juli 2021, kegiatan dilaksanakan di Dinas Kesehatan Kabupaten Enrekang. Hasil pelatihan menunjukkan bahwa pengetahuan dan kemampuan pengelola keuangan Puskesmas dalam mengelola dan melaporkan aktivitas keuangan yang merupakan tanggung jawab utama mereka, telah meningkat.